2021
DOI: 10.1186/s12889-021-10746-4
|View full text |Cite
|
Sign up to set email alerts
|

Colon cancer survival differs from right side to left side and lymph node harvest number matter

Abstract: Background Right-sided colorectal cancer (CRC) has worse survival than does left-sided CRC. The objective of this study was to further assess the impact of right-side location on survival and the role of the extent of lymphadenectomy. Methods All CRCs diagnosed between 2000 and 2012 in Emilia-Romagna Region, Italy, were included. Data for stage, grade, histology, screening history, and number of removed lymph nodes (LN) were collected. Multivariabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 28 publications
3
28
2
Order By: Relevance
“…Other sociodemographic groups at increased risk of CRC include obese individuals, and in particular obese women, who are less likely to undergo screening as compared to their normal weight counterparts 13 . Although existing data show that RsCC disproportionately affects Black individuals and women, the relationship between obesity and CRC sidedness remains to be established 14–17 . We aimed to evaluate the influence of overweight and obesity on CRC sidedness.…”
Section: Introductionmentioning
confidence: 99%
“…Other sociodemographic groups at increased risk of CRC include obese individuals, and in particular obese women, who are less likely to undergo screening as compared to their normal weight counterparts 13 . Although existing data show that RsCC disproportionately affects Black individuals and women, the relationship between obesity and CRC sidedness remains to be established 14–17 . We aimed to evaluate the influence of overweight and obesity on CRC sidedness.…”
Section: Introductionmentioning
confidence: 99%
“…The AJCC seventh edition recommends that lymph node status should be assessed by N staging system, patients were divided into N0, N1, N2 three stages according to the number of metastatic lymph nodes. However, on account of various factors such as tumor site, examination of lymph node status is not adequate in some patients, 9 which could disturb lymph node staging to predict patient prognosis. Michal found that examined lymph nodes was less in left‐sided colon cancer patients, which might result in incorrect lymph node staging and thus inaccurate prediction of long‐term outcomes 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The difference in prognosis among RCC, LCC, and RECC patients is notable, with most studies confirming that RCC patients have poorer prognosis compared to patients with LCC and RECC (5,14,(18)(19)(20). Furthermore, the intestinal flora, clinical manifestations, and treatment responses of patients with RCC, LCC, and RECC vary considerably (18,19).…”
Section: Discussionmentioning
confidence: 99%